2010
DOI: 10.1086/649782
|View full text |Cite
|
Sign up to set email alerts
|

Protein E ofHaemophilus influenzaeIs a Ubiquitous Highly Conserved Adhesin

Abstract: Protein E (PE) of nontypeable Haemophilus influenzae (NTHi) is involved in adhesion and activation of epithelial cells. A total of 186 clinical NTHi isolates, encapsulated H. influenzae, and culture collection strains were analyzed. PE was highly conserved in both NTHi and encapsulated H. influenzae (96.9%-100% identity without the signal peptide). PE also existed in other members of the genus Pasteurellaceae. The epithelial cell binding region (amino acids 84-108) was completely conserved. Phylogenetic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 17 publications
1
34
0
Order By: Relevance
“…Because clinical NTHi isolates express the adhesion protein PE, we hypothesized that PE is a plasminogen-binding protein (21). Consequently, binding of plasminogen to recombinant PE, to the PE knockout strain, and to PE expressed on the surface of E. coli was tested.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because clinical NTHi isolates express the adhesion protein PE, we hypothesized that PE is a plasminogen-binding protein (21). Consequently, binding of plasminogen to recombinant PE, to the PE knockout strain, and to PE expressed on the surface of E. coli was tested.…”
Section: Discussionmentioning
confidence: 99%
“…Because NTHi 3655 isolates express PE on their surface (21), this bacterial surface and adhesion protein was considered as a candidate ligand for plasminogen. Therefore, binding of plasminogen to recombinant PE was assayed.…”
Section: Pe Is a Plasminogen-binding Protein Of Nthimentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, immunization with the PE amino acid (aa) 84 to 108 peptide showed significantly better pulmonary clearance in a mouse model than immunization with an unrelated control peptide (12). When the pe gene was sequenced in all Haemophilus spp., including Hib and NTHI clinical isolates, we found that PE is a ubiquitous Haemophilus outer membrane protein (13). The active vitronectin-binding region PE aa 84 to 106 was found to be 100% conserved.…”
mentioning
confidence: 85%
“…influenzae protein E (PE) is a 16 kDa, highly conserved (96.9%-100%), ubiquitous outer membrane lipoprotein that exists in both encapsulated H. influenzae and NTHi (Singh et al, 2010). PE was initially described as an adhesin that binds to epithelial cells of different origins including those from COPD patients (Ronander et al, 2009).…”
Section: Introductionmentioning
confidence: 99%